Refractory depression – mechanisms and efficacy of radically open dialectical behaviour therapy (RefraMED): findings of a randomised trial on benefits and harms. (April 2020) - Lynch, Thomas R.; Hempel, Roelie J.; Whalley, Ben; Byford, Sarah; Chamba, Rampaul; Clarke, Paul; Clarke, Susan; Kingdon, David G.; O'Mahen, Heather; Remington, Bob; Rushbrook, Sophie C.; Shearer, James; et al.
Abstract : Background: Individuals with depression often do not respond to medication or psychotherapy. Radically open dialectical behaviour therapy (RO DBT) is a new treatment targeting overcontrolled personality, common in refractory depression. Aims: To compare RO DBT plus treatment as usual (TAU) for refractory depression with TAU alone (trial registration: ISRCTN 85784627). Method: RO DBT comprised 29 therapy sessions and 27 skills classes over 6 months. Our completed randomised trial evaluated RO DBT for refractory depression over 18 months in three British secondary care centres. Of 250 adult participants, we randomised 162 (65%) to RO DBT. The primary outcome was the Hamilton Rating Scale for Depression (HRSD), assessed masked and analysed by treatment allocated. Results: After 7 months, immediately following therapy, RO DBT had significantly reduced depressive symptoms by 5.40 points on the HRSD relative to TAU (95% CI 0.94–9.85). After 12 months (primary end-point), the difference of 2.15 points on the HRSD in favour of RO DBT was not significant (95% CI –2.28 to 6.59); nor was that of 1.69 points on the HRSD at 18 months (95% CI –2.84 to 6.22). Throughout RO DBT participants reported significantly better psychological flexibility and emotional coping than controls. However, they reported eight possible serious adverse reactions compared with none in the control group. Conclusions: The RO DBT group reported significantly lower HRSD scores than the control group after 7 months, but not thereafter. The imbalance in serious adverse reactions was probably because of the controls' limited opportunities to report these.